Effect of High-Pressure Torsion on Phase Formation and Mechanical Properties of a High-Entropy TiZrHfMoCrCo Alloy - Gornakova, Alena S.; Kabirova, Dilara B.; Korneva, Anna; Straumal, Boris; Imayev, Marcel F.; Kuzmin, Alexei; Czaja, Paweł; Afonikova, Natalia S.; Orlov, Valeriy I.; Nekrasov, Alexei N.; Khayretdinov, Nafis F.; Davdian, Gregory (MDPI, 2023)
This investigation delved into the alterations in the mechanical properties of a TiZrHfMoCrCo high-entropy alloy due to phase transformations induced by high-pressure torsion (HPT). The alloy’s genesis involved levitation melting within an argon atmosphere, presenting two distinct states for analysis: the initial, post-manufacturing state and the state subsequent to HPT treatment. The original alloy featured a composition comprising a singular A2 phase with a bcc lattice and two Laves phases, C15 and C14. The HPT process triggered significant phase modifications: a retention of one C15 Laves phase and decomposition of the bcc phase into two distinct phases exhibiting different bcc lattice parameters. The HPT-induced effect prominently manifests as strong grain refinement. However, scanning electron microscopy (SEM) observations unveiled persistent inhomogeneities at a micron scale both before and after HPT treatment. Thus, grain refinement occurs separately within each of the bcc and Laves phases, visible in the light, dark, and gray areas in SEM images, while mixing does not occur on the scale of several microns. The examination of Ti, Cr, Co, Zr, Mo, and Hf via X-ray absorption spectroscopy (EXAFS) at specific K-edges and L3-edge revealed that the HPT treatment conserves the local atomic environment of metal atoms, albeit with a slight elevation in static disorder. Assessments through microhardness and three-point bending tests demonstrated the material’s inherent hardness and brittleness. The microhardness, standing at a substantial value of 600 HV, displayed negligible augmentation post-HPT. However, the microhardness of individual phases exhibited a notable alteration, nearly doubling in magnitude. © 2023 by the authors. --//-- This is an open-access article: Gornakova, A.S.; Kabirova, D.B.; Korneva, A.; Straumal, B.; Imayev, M.F.; Kuzmin, A.; Czaja, P.; Afonikova, N.S.; Orlov, V.I.; Nekrasov, A.N.; et al. Effect of High-Pressure Torsion on Phase Formation and Mechanical Properties of a High-Entropy TiZrHfMoCrCo Alloy. Materials 2023, 16, 7558. https://doi.org/10.3390/ma16247558 published under the CC BY 4.0 licence.
This research was funded by the Russian Ministry of Science and Higher Education (contract no. 075-15-2021-945; grant no. 13.2251.21.0013). We acknowledge DESY (Hamburg, Germany), a member of the Helmholtz Association HGF, for the provision of experimental facilities. Parts of this research were carried out at the PETRA III P65 beamline.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; high-entropy alloy; EBSD; EXAFS; crystal lattice; phase transformations; three-point bending; microhardness